Efficacy of 1.5% Dish Washing Solution and 95% Lemon Water in Substituting Perilous Xylene as a Deparaffinizing Agent for Routine H and E Staining Procedure: A Short Study - Anuradha Ananthaneni; Srilekha Namala; Vijay Srinivas Guduru; V. V. S. Ramprasad; Sabitha Devi Ramisetty; Urmila Udayashankar; Kiran Kumar Naik (Scientifica)
Aim. To assess the efficacy of dish washing solution and diluted lemon water in deparaffinizing sections during conventional hematoxylin and eosin staining technique. Objective. The objective is to utilize eco-friendly economical substitute for xylene. Materials and Methods. Using twenty paraffin embedded tissue blocks, three sections each were prepared. One section was stained with conventional H and E method (Group A) and the other two sections with xylene-free (XF) H and E (Groups B and C). Staining characteristics were compared with xylene and scoring was given. Total score of 3–5 was regarded as adequate for diagnosis and less than that inadequate for diagnosis. Statistical Analysis. Chi-square test, Kruskal Wallis ANOVA test, and Mann-Whitney U test were used. Results. Adequacy of nuclear staining, crispness, and staining for diagnosis were greater in both Groups A and C (100%) than Group B (95%). Adequacy of cytoplasmic staining was similar in all the three groups (100%). Group B showed comparatively superior uniform staining and less retention of wax. Conclusion. Dish washing solution or diluted lemon water can be replaced for xylene as deparaffinizing agent in hematoxylin and eosin procedure.